2011
DOI: 10.1111/j.1471-0307.2011.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of incorporating wild-type strains of Lactococcus lactis into Turkish white-brined cheese (Beyaz peynir) on the fatty acid and volatile content

Abstract: The development of free fatty acids (FFA) and volatile flavour compounds in the Turkish white‐brined cheese Beyaz peynir made by using three wild strains of Lactococcus lactis subsp. lactis was investigated over 90 days. Results showed that production of both FFA and flavour compounds in the control (PK1) and experimental cheeses (MBLL9, MBLL23 and MBL27) was strain dependent. The hydrolysis of milk fat was more evident in the cheese made using Lc. lactis subsp. lactis MBL27. Considering the production of fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Similarly, ethyl butanoate, ethyl hexanoate, ethyl octanoate and ethyl lactate were identified at the highest concentrations in Malatya cheese (a native cheese variety in Turkey) at 90 days of ripening . Concentrations of ethyl butanoate increased significantly during ripening both in cheeses B and C. Ethyl acetate is responsible for the fruity and pineapple aroma in cheese (Ozer et al 2011). Ethyl octanoate was found only in 90 or 120-day-old cheeses.…”
Section: Estersmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, ethyl butanoate, ethyl hexanoate, ethyl octanoate and ethyl lactate were identified at the highest concentrations in Malatya cheese (a native cheese variety in Turkey) at 90 days of ripening . Concentrations of ethyl butanoate increased significantly during ripening both in cheeses B and C. Ethyl acetate is responsible for the fruity and pineapple aroma in cheese (Ozer et al 2011). Ethyl octanoate was found only in 90 or 120-day-old cheeses.…”
Section: Estersmentioning
confidence: 92%
“…The second most abundant carboxylic acid at 120 days of ripening was butanoic acid, which has rancid, cheesy odours and probably contributes a ripe aroma in cheese (Yvon and Rijnen 2001). Butanoic acid was identified as the most abundant volatile fraction in Feta cheeses (Kondyli et al 2012), and other carboxylic acids including acetic and hexanoic acids were found to be the major acids in the Turkish white-brined cheeses (Ozer et al 2011).…”
Section: Carboxylic Acidsmentioning
confidence: 98%
“…Therefore, the screening for new strains for cheese-making has become a subject of interest during the last 20 years or more. [3] In Turkey, there are more than 50 local cheese varieties, but few of them have commercial importance. Urfa cheese-a semi-hard brined type variety native to Southeastern Anatolia region of Turkey-is mainly produced locally from raw milk by smallscale dairies, but is widely marketed in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…These cheeses are either consumed fresh or ripened according to the traditional characteristics of the product. For example, fresh classic white cheese produced from cow’s milk is taken to the market with minimum a three-week ripening, while Ezine-type white cheese can have a ripening period of up to 6 months ( 2 ). Therefore, determining the quality characteristics of the cheese is important to monitor the degree of ripening of the cheese.…”
Section: Introductionmentioning
confidence: 99%
“…Cheese ripening involves various biochemical and microbiological changes by the metabolism of starter cultures, indigenous, clotting, adjunct enzymes, and ripening accelerating agents. The biochemical reactions that occur during cheese ripening can be classified into three main categories: (1) the catabolism of residual lactose and citrate into organic acids and other components (glycolysis); (2) the catabolism of proteins into amino acids and other amin products (proteolysis); and (3) the catabolism of the fat into fatty acids and other further lipolysis compounds (3,4).…”
mentioning
confidence: 99%